The Association of Body Mass Index and Incidence of Diabetic Retinopathy in newly diagnosed Type 2 diabetes: A longitudinal Study in Karachi - Ahmed, Iftikhar; Anna Mustafa; Zainab Hussain; Zainab Junaid; Muhammad Nizamuddin (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To elucidate the relationship between BMI, 25-29.9 kg/m²/obesity, and the incidence of Diabetic Retinopathy (DR) among DM patients. METHODOLOGY: This is a prospective cohort study. The newly diagnosed type 2 diabetes mellitus patients were enrolled, with a baseline of 1675 subjects. Systematic random sampling was used to select the recruited patients at the Ophthalmology Department of Sindh Government Qatar Hospital, Karachi. Incident diabetic retinopathy (DR) was determined if any of the photos received a high rating for DR. Exclusively, participants with DR grades available results from the 2022 subsequent examinations were considered for inclusion in this study. Diabetic Retinopathy (DR) is classified into five stages per the ICDR scale: (1) no retinopathy, (2) mild NPDR, (3) moderate NPDR, (4) severe NPDR, and (5) PDR. BMI criteria: <25 kg/m² (normal/underweight), 25–29.9 kg/m² (overweight), and ?30 kg/m² (Obese). Univariate and multivariate logistic regression models were employed by SPSS version 27. RESULTS: In total, a mean (SD) age of 61(7.5) years. Of these participants, 59.5% were male. A significant number of the participants were <25 kg/m² 821(49%). 856 (51%) of the patients came for follow-up after approximately 365 days. Diabetic Retinopathy was present in 197 (23%) of the patients. CONCLUSION: In summary, our study, conducted within a substantial cohort of adults, demonstrated a correlation between higher Body Mass Index (BMI) and an increased risk of incident Diabetic Retinopathy (DR) over a 1-year follow-up period.